Engineering PEGylated polyester nanoparticles to reduce complement-mediated infusion reaction - Maisha, Nuzhat; Naik, Nidhi; Okesola, Mawuyon; Coombs, Tobias; Zilberberg, Rose; Pandala, Narendra; Lavik, Erin (ACS, 2021)
Translation of intravenously administered nanomaterials to the clinic is limited due to adverse infusion reactions. While these reactions are infrequent, with up to 10% prone to experiencing infusion reactions, the reactions can be severe and life-threatening. One of the innate immune pathways, the complement activation pathway, plays a significant role in mediating this response. Nanoparticle surface properties are a relevant design feature, as they control the blood proteins the nanoparticles interact with and allow the nanoparticles to evade the immune reaction. PEGylation of nanosurfaces is critical in improving the blood circulation of nanoparticles and reducing opsonization. Our goal was to understand whether modifying the surface architecture by varying the PEG density and architecture can impact the complement response in vitro. We utilized block copolymers of poly(lactic acid)-b-poly(ethylene glycol) prepared with poly(ethylene glycol) macroinitiators of molecular weights 3400 and 5000 Da. Tracking the complement biomarker C5a, we monitored the impact of changing PEGylation of the nanoparticles. We also investigated how the changing PEG length on the nanoparticle surface impacts further strengthening the stealth properties. Lastly, we determined which cytokines change upon blood incubation with nanoparticles in vitro to understand the extent to which inflammation may occur and the crosstalk between the complement and immune responses. Increasing PEGylation reduced the generation of complement-mediated anaphylatoxin C5a in vitro, with 5000 Da PEG more effectively reducing levels of C5a generated compared to 3400 Da PEG. The insights gathered regarding the impact of PEG density and PEG chain length would be critical in developing stealth nanoparticles that do not lead to infusion reactions upon intravenous administration.